An approach to optimization of enzymatic hydrolysis from sugarcane bagasse based on organosolv pretreatment - Mesa, Leyanis (2010)
The organosolv pretreatment followed by enzymatic hydrolysis of the pretreated material and subsequent fermentation of the hydrolysate produced, was the strategy used for ethanol production from sugarcane bagasse. The effect of different operational variables affecting the pretreatment (the catalyst type and its concentration, and the pretreatment time) and enzymatic hydrolysis stage (substrate concentration, cellulase loading, addition of xylanase and Tween 20, and the cellulase/β-glucosidase ratio), were investigated. RESULTS: The best values of glucose concentration (28.8 g L−1) and yield (25.1 g per 100 g dry matter) were obtained when the material was pretreated with 1.25% (w/w) H2SO4 for 60 min, and subsequently hydrolyzed using 10% (w/v) substrate concentration in a reaction medium supplemented with xylanase (300 UI g−1) and Tween 20 (2.5% w/w). Fermentation of the broth obtained under these optimum conditions by Saccharomyces cerevisiae resulted in an ethanol yield of 92.8% based on the theoretical yield, after 24 h. CONCLUSION: Organosolv pretreatment of sugarcane bagasse under soft conditions, and subsequent enzymatic hydrolysis of the pretreated material with a cellulolytic system supplemented with xylanase and Tween 20, is a suitable procedure to obtain a glucose rich hydrolysate efficiently fermentable to ethanol by Sacharomyces cerevisiae yeasts.